Public space as ‘context’ in assistive information and communication technologies for people with cognitive impairment - Adkins, B.; Smith, Dianne; Barnett, K.; Grant, E. (Routledge Taylor & Fancis, 2006)
This paper examines emergent issues of ‘context’ raised by the application of information and communication technologies for people with cognitive impairment. The issue of the development and application of cognitive prostheses for this group provides an opportunity to examine assumptions and issues emerging from this area pertaining to understandings of the term ‘context’ in these applications. In this sense the paper takes these assumptions and issues as a point of departure for the development of a ‘problematic’ that can contribute to the study of the experience of cognitive impairment. The paper specifically addresses recent concerns about the lack of knowledge of these experiences in public spaces such as shopping centres, given that this is a critical site for the civic participation of this group. We argue that this participation should be understood in terms of the ‘meeting of two histories’: the history of contemporary requirements governing participation in public space and the habitus of people with cognitive impairment with regard to this participation. The paper proposes that the salience of cognitive impairment in these spaces turns on what it means for individuals to inhabit them as complex ‘Container Technologies’ (Sofia) and underlines the importance of understanding their efforts to attain a sense of normality (Goffman) in these contexts. We propose that this approach can inform research contributing to the development of a ‘pattern language’, informing applications that make cognition a system property in networks that operate between humans, machines and their contexts.